PENERAPAN PENDEKATAN PEMBELAJARAN STUDENT TEAMS ACHIEVEMENTS DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SDN 035 TARAIBANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Iswati, Iswati (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
This research is motivated by the difficulty in teaching geometry caused by the learning that is not appropriate, so students’ mathematics learning results are low. For that reason, there is a need to improve learning by applying the Student Team Achievement Division (STAD) learning approach. The purpose of this study is to improve the mathematical learning results of fifth-grade students of SDN 035 Taraibangun, Kampar, through the application of the STAD cooperative learning approach. This research is a classroom action research (CAR) consisting of two cycles and its implementation is in the fifth grade. The location of this research is carried out at SDN 035 Taraibangun, Kampar. Data collection has been done using test items and observation sheets. The results showed that in the initial cycle before learning using the STAD approach, student mathematics learning results were low with an average score of 58. After the implementation of the STAD approach, students’ learning results in the first cycle increased with an average value of 84, and the results of observation sheets showed that students could work with their groups and know their peers. Then, in the second cycle, the students’ learning results increased to 91. In addition, the results of observations showed that the students worked with their groups and were familiar with peer tutors. Therefore, the research hypothesis is accepted. It means that the application of STAD could improve mathematics learning results about the volume for the fifth-grade students at SDN 035 Taraibangun, Kampar.